2013
DOI: 10.3109/14767058.2013.858688
|View full text |Cite
|
Sign up to set email alerts
|

Maternal magnesium level effect on preterm labor treatment

Abstract: Basal magnesium levels in preterm labor had a predictive value in evaluating MgSO4 tocolysis response. It may help to select patients who are appropriate for MgSO4 tocolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
3
21
0
1
Order By: Relevance
“…Similar findings were reported by Shahid et al (29), Uludag et al (25), Okunade et al (8), Kamal et al (13), Bhat and Waheed (31). In Okunade's study, the mean of serum magnesium level was 1.73±0.4 versus 1.93 ± 0.4 mg/dL in the case and control groups, respectively (8).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar findings were reported by Shahid et al (29), Uludag et al (25), Okunade et al (8), Kamal et al (13), Bhat and Waheed (31). In Okunade's study, the mean of serum magnesium level was 1.73±0.4 versus 1.93 ± 0.4 mg/dL in the case and control groups, respectively (8).…”
Section: Discussionsupporting
confidence: 87%
“…In their study, Uludag et al reported similar findings and concluded that basal serum magnesium level had a predictive value in evaluating MgSO4 response to tocolysis (25). Other studies suggested that serum magnesium level in pregnancy could be a valuable tool in predicting preterm onset of labor (29,30) and some suggested prophylactic oral magnesium supplementation in women with higher risk for the development of preterm labor (8,14,32).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…24 Uludağ et al found basal serum magnesium was significantly lower in successful preterm labour group in whom contractions ceased with magnesium sulfate tocolysis 1.6 versus 1.9 mg/dl for unsuccessful preterm labour group whose contractions increased and delivered preterm despite magnesium sulfate tocolysis (p value <0.001) and a cut off value of <1.75 mg/dl had a significant predictive value for better identifying a positive response to tocolytic magnesium sulfate. 25 Regarding magnesium level at different gestational age, we found that in 28-30 weeks, although it was higher in group II but statistically non-significant unlike Shakura et al who found it highly significant, probably because of different dietary habits in our society, while it was lower in group I compared to group II in gestational age 31-33 and 34-36 weeks and the difference was statistically significant like Shakura et al, which may due to increased demand with the advance of pregnancy. 26 We observed that there was a decrease in serum magnesium with progression of pregnancy in both groups in agreement with observation of other investigators.…”
Section: Discussionmentioning
confidence: 99%